Retraction Note: Engaging in Short-Term Moderate-Intensity Exercise Increases Growth Hormone Levels in Individuals with Obesit (Physical Education Theory and Methodology, 24(4), 619–625. https://doi.org/10.17309/tmfv.2024.4.14) - Editorial Team (Physical Education Theory and Methodology)
The Editors have retracted the following article: